A new flavonoid glycoside and potential antifungal activity of isolated constituents from the flowers of Lilium lancifolium. (1st May 2015) - Xu, Haifeng; Zhao, Bo; Wang, Yafei; Lin, Ningning; Wang, Libing; Song, Tiejun; Yang, Huijun
Lancifolide A, 4′, 7-dimethoxyisorhamnetin-3-O-α-L-rhamnosyl (1→2)[α-L-arabinosyl (1→6)]-β-D-glucopyranoside, a new flavonoid glycoside, has been isolated from the flowers of Lilium lancifolium, along with five known flavonoid glycosides, which were reported to be obtained for the first time from this plant. Their structures were elucidated on the basis of spectroscopic methods and from literature values. All components were tested for antifungal activity.